PEMETAAN TINGKAT RESIKO GEMPABUMI DAERAH LIWA DAN SEKITARNYA BERDASARKAN PENGUKURAN MIKROTREMOR THE RISK LEVEL MAPPING OF EARTHQUAKE IN LIWA AND VINICITY BASED ON MICROTREMOR MEASURMENT - , Lidia Hartati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Microtremor measurments have been conducted in Liwa and vinicity, Lampung Barat, Lampung. This measurment is performed to determine the risk level distribution of earthquake based on Peak Ground Acceleration (PGA) , which is supported by dominan period To values, amplification , ground seismic vulnerability index , sediment layer thickness and ground shear strain .The measurements were performed by Geological Survey Center (PSG) Bandung, by using three componens seismometer Lennartz type 0.2 Hz SARA at 66 points. The data analysis using Horizontal to Vertical Spectral Ratio (HVSR) method. The results of the HVSR analysis are the dominan frequency and amplification . Then the calculation of the ground seismic vulnerability index, sediment layer thickness, PGA and ground shear strain. The calculate of PGA values using by Kanai empirical equations for earthquake February 12, 1994 event. Then the calculation performed of the risk level of earthquake. The results show that the Liwa and vinicity have PGA values rangs from 123.5â483.5 gal or VII-IX Modified Mercalli Intensity (MMI). Dominan period values rangs from 0.1â1.6 second, amplification values rangs from 2.4â5.6, thickness sediment layer values rangs from 11.1â203.1 meters, the ground seismic vulnerability index values rangs from 0.9â58.5 second and ground shear strain values rangs from 0.004â0.133 gal second. Based on the risk level classification of earthquake from these data, can be concluded that the Liwa and vinicity vulnerable of the earthquake, which has the risk level is from the big risk one to the bigger risk one, with proven scala VII-IX MMI and IX-X MMI. Key words: Microtremor, HVSR, PGA, Sediment Layer Thickness, Ground Seismic Vulnerability Index, Ground Shear Strain.